Extraction of oil from solid fat of silver catfish (pangasianodon hypophthalmus) waste by centrifugation - Muhammad Aziq, Mohd Azmi; Rohana, Abu (Malaysian Society of Applied Biology, 2023)
Oil extracted from fish waste could be a source of valuable fatty acids such as saturated (SFAs), monounsaturated (MUFAs), and polyunsaturated fatty acids (PUFAs). In this study, the solid fat from silver catfish (Pangasianodon hypophthalmus) waste was used to extract oil by centrifugation using different extraction solvent (distilled water, 70% ethanol, 70% acetone and 70% cyclohexane), rotation time (15, 25, 35 & 45 min), rotational speed (2000, 4000, 6000, 8000 & 10000 r.p.m) and rotational temperature (5, 10, 15, 20 & 25 °C). The compositions of fatty acids in the extracted oil were determined by gas chromatography-mass spectrometry (GC-MS) analysis. The highest oil yield of 156.7 ± 16.7 mg/g was achieved by centrifugation at 10000 r.p.m, 25 °C for 15 min using 70% acetone. The extracted oil contains 0.0223 mg/g palmitic acid, 0.0216 mg/g steric acid, and 0.0262 mg/g oleic acid. However, the essential PUFAs such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) could not be detected by GC-MS analysis. This study found that the fish oil extracted from the solid fat of the silver catfish waste can be used as a potential source of palmitic acid, stearic acid, and oleic acid.